Modern technologies and their role in promoting Algerian tourism - Khadidja fedoul; Mohamed touhami kkadi (Social Empowerment Journal, 2023)
Information and communication technology has witnessed conflicting developments affecting various aspects of human; economic and social life tourisms an important source for achieving economic development especially recently, as it is consider source. and an essential element to attract tourists, and it is necessary to pay attention to it and work to develop this sensitive sector tourist areas and provide electronic service that facilitate the tourist to roam comfortably… through this presentation we ask the following question: How do modern technologies contribute to the promotion of tourism in Algeria?